Is FDI a Safer Form of Financing? - Eduardo Fernández-Arias; Ricardo Hausmann (Inter-American Development Bank, Research Department, 2000)
It has been common to attribute financial crises to short-term capital inflows, while foreign direct investment (FDI) is seen as a safer form of finance. The relationship between crises and the composition of capital flows is particularly relevant at present because the flow of capital to Latin America is becoming increasingly dominated by FDI. This paper asks whether the composition of capital inflows and of the stock of foreign liabilities is relevant for financial crises, be it their frequency, depth, or length. It explores the possible role of FDI as a benign form of external liability relative to other classes of liabilities, reviewing both analytical and empirical arguments.
Keywords: 330; Auslandsinvestition; Kapitalimport; Internationale Finanzierung; Schwellenländer; Lateinamerika